Australian English listeners' perception of Japanese vowel length reveals underlying phonological knowledge - Yazawa, Kakeru; Whang, James; Escudero, Paola (Frontiers in Psychology, 2023)
Speech perception patterns are strongly influenced by one's native phonology. It is generally accepted that native English listeners rely primarily on spectral cues when perceiving vowels, making limited use of duration cues because English lacks phonemic vowel length. However, the literature on vowel perception by English listeners shows a marked bias towards American English, with the phonological diversity among different varieties of English largely overlooked.The current study investigates the perception of Japanese vowel length contrasts by native listeners of Australian English, which is reported to use length to distinguish vowels unlike most other varieties of English. Twenty monolingual Australian English listeners participated in a forced-choice experiment, where they categorized Japanese long and short vowels as most similar to their native vowel categories. The results showed a general tendency for Japanese long and short vowels (e.g., /ii, i/) to be categorized as Australian English long and short vowels (e.g., /i:, I/ as in "heed," "hid"), respectively, which contrasts with American English listeners' categorization of all Japanese vowels as tense regardless of length (e.g., /ii, i/ as both "heed") as reported previously. Moreover, this duration-based categorization was found not only for Australian English categories that contrast in duration alone (e.g., /5:, 5/ as in "hard," "hud") but also for those that contrast in both duration and spectra (e.g., /o:, O/ as in "hoard," "hod"), despite their spectral mismatch from the corresponding Japanese vowels (e.g., /aa, a/ and /oo, o/). The results, therefore, suggest that duration cues play a prominent role across all vowel categories-even nonnative-for Australian English listeners. The finding supports a featurebased framework of speech perception, where phonological features like length are shared across multiple categories, rather than the segment-based framework that is currently dominant, which regards acoustic cues like duration as being tied to a specific native segmental category.Implications for second and foreign language learning are discussed.